Brazil: An empirical study on fiscal policy transmission - Tito Belchior Silva Moreira (CEPAL Review, 2011)
This article sets out to empirically determine whether the ratio between debt and gross domestic product (gdp) affected real and nominal variables such as the demand for money, the nominal interest rate, investment and the output gap, between January 1995 and March 2008. The specific aim is to identify fiscal-policy transmission channels and decide whether this policy was active or passive in the period in question. The study finds empirical evidence that fiscal policy was active and monetary policy passive —features that characterize a non-Ricardian model.